Religion in American Presidential Campaigns, 1952-2016: Applying a New Framework for Understanding Candidate Communication - Chapp, Christopher (Journal for the scientific study of religion, 2019)
The content and impact of religious communication in politics has been a topic of increasing public and scholarly interest in recent years. To provide a foundation for future research in this area, the present study theorizes five broad factors-historical trajectory, party expectations, audience religiosity, candidate attributes, and opponent strategy-that may help explain why political candidates use religious language. We employ this framework in a large-scale computer-assisted content analysis of U.S. presidential campaign speeches from 1952 to 2016. Findings reveal that the Reagan shift observed in prior research was driven specifically by God language, that the "God gap" between Democrats and Republicans is modest and topic-specific, and that audience characteristics are crucial in explaining candidates' religious communication.